Evaluasi Tingkat Terhadap Pengetahuan Sikap dan Tindakan terhadap Swamedikasi : Studi Kasus Kecamatan Una-Una Provinsi Sulawesi Tengah - Dizky Ramadani Putri Papeo; Teti Sutriati Tuloli (Journal Syifa Sciences and Clinical Research, 2023)
Self-medication is an attempt to use drugs by a person to treat ailments or minor symptoms such as fever, dizziness, cough, influenza, and other diseases using modern and traditional medicines without a doctor's prescription or recommendation.The purpose of this study was to describe the knowledge, attitudes, and actions of self-medication carried out by the community. This was a descriptive cross-sectional study with a total sample of 93 respondents taken by purposive sampling. Data were collected by filling out a questionnaire that had been tested for validity and reliability.The results showed that the majority of respondents in Una-Una District, Central Sulawesi Province were women (57%) with a majority age range between 40 - 50 years (33%), with High School/Vocational/Islamic High School educational background (33%), and had different jobs (40%). The level of knowledge, attitudes, and actions of the community regarding self-medication was classified as good with the percentage of the knowledge level of 61%, the attitude level of 57%, and the level of action of 74%.